Seismic hazard assessment and volcanogenic seismicity for the Democratic Republic of Congo and surrounding areas, Western Rift Valley of Africa - Tuluka, Georges Mavonga (My University, 2011)
The Western Rift Valley of Africa has experienced several severe earthquakes with magnitude M≥6 and volcanic eruptions in recent historical times. Most of these earthquakes occurred in the Democratic Republic of Congo (DRC) and neighbouring countries such as Uganda and Tanzania. The largest earthquake on record, which occurred at Kasanga (Tanzania) on 13 December 1910 in the Lake Tanganyika area, had a magnitude of Ms7.3. The most recent significant earthquake occurred approximately 20 km north of Bukavu City (DRC) on 03 February 2008 with magnitude Mw=6.0 in the Basin of Lake Kivu. The Virunga volcano group, located at the northern edge of Lake Kivu, consists of eight major volcanoes (Muhavura, Gahinga, Sabinyo, Visoke, Karisimbi, Mikeno, Nyiragongo and Nyamuragira). The volcanoes Nyiragongo and Nyamuragira have been the most active since 1882. A probabilistic approach was used to map the seismic hazard in Democratic Republic of Congo and surrounding areas, and assess the seismic hazard level for 14 cities in the region. Seismic hazard maps for 2%, 5% and 10% chance of exceedance of the indicated ground accelerations in 50 years were prepared using a 90-year catalogue compiled for homogeneous magnitudes (Mw); the attenuation relations of Mavonga (for the Western Rift Valley of Africa), Atkinson and Boore (for eastern and North America) and Jonathan (for eastern and southern Africa); and the EZ-Frisk software package. A Poisson model of earthquake occurrence that assumes that events are independent was adopted. Therefore, foreshocks, aftershocks and earthquake swarms were removed from the initial catalogue of 2249 events. Furthermore Mw=4 was selected as the lower magnitude bound (Mmin) because smaller earthquakes are considered unlikely to cause damage, even to houses that are poorly designed and built. Thus, any remaining events with Mw<4 were also excluded from the catalogue, leaving a sub-catalogue of 821 events The highest estimated levels of seismic hazard were found in the Lake Tanganyika Rift seismic zone, where peak ground accelerations (PGA) in excess of 0.32g, 0.22g and 0.16g are expected to occur with 2%, 5% and 10% chance of exceedence in 50 years, respectively. The seismic hazard in the Congo basin diminishes with distance away from the Western Rift Valley until, at a distance of about 450 km, the chance of exceeding 0.05 g (the threshold value of engineering interest) is less than 10% in 50 years. Finally, from the probabilistic seismic hazard analysis of the DR Congo and surrounding areas, four seismic zones were identified and rated as follows: Zone A (very high hazard), Zone B (high hazard), Zone C ( moderate hazard), and Zone D (low hazard). The zone A includes the Lake Tanganyika Rift zone where PGA values of 0.32g, 0.22g and 0.16 g are expected to occur with probability 2%, 5% and 10% in 50 years, respectively. Zone B includes the Lake Kivu Basin, Mount Ruwenzori and Lake Edouard region. Zone C includes Rutsuru, Masisi, Upemba area and a part of the Congo basin close to the Western Rift. The remainder of the Congo basin constitutes the zone D. To understand how volcanoes work and reduce the risk due to the Virunga volcanic eruptions in the Western Rift Valley of Africa, the crustal structure beneath the Virunga volcanic area was investigated and studies of volcanogenic seismicity were carried out. From these studies, it was found: High velocity material (6.9 to 7.3 km/s) lies beneath the Kunene (KNN) and Kibumba (KBB) broadband stations at depths of 3-20 km and 3-10 km, respectively, which is indicative of magma cumulates within the volcanic edifice. A low velocity zone was observed below KNN and KBB at depths of 20-30 km and 18-28 km, respectively, and with average velocity 6.1 km/s and 5.9 km/s. This low velocity zone may sample the magma chamber or a melt-rich sill. The depth of the crust-mantle transition zone beneath the area sampled by the KNN and KBB in the Virunga area was determined to be about 39 to 43 km and 30 to 39 km, respectively. Swarm-type seismicity composed mainly of long-period volcanic earthquakes preceded the eruptions of Nyamuragira volcano and was probably enhanced by tectonic seismicity related to rifting. A steady increase in seismicity at a constant rate from a deep magma feeder (located at about 20 to 30 km depth) was observed ten or eleven months before eruption. In the last stage (1 or 2 months) before the eruption, the hypocenters of long-period volcanic earthquakes became shallower. The new model of the local crustal seismic velocity for the Virunga area is useful to map the migration of hypocenters of earthquakes accurately and reveals trends that could be precursors of volcanic eruptions This pattern of seismicity prior to the volcanic eruptions, integrated with other available data (e.g. INSAR, GPS), may be used to characterize the volcanic process and forecast volcanic eruptions in the Virunga area.